Effect of depression disorder on the efficacy and quality of life of first-line chemotherapy combined with immunotherapy in oncogene-driver negative NSCLC patients - Li, Wen; Bi, Ziran; Wu, Junxu; Duan, Xu; Pang, Lulian; Jing, Yanyan; Yin, Xiangxiang; Cheng, Huaidong (Frontiers in Oncology, 2022)
Objective: To evaluate the relationships between psychological distress and immunotherapy combined with chemotherapy efficacy, adverse reactions and quality of life scores in patients with advanced non-small cell lung cancer (NSCLC). Methods:A total of 104 NSCLC patients were enrolled who received 4-6 cycles of standard immunotherapy , of whom 67 were immunized in combination with chemotherapy, were evaluated with the Distress Thermometer (DT) and European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30). The aim was to analyze the correlation between psychological distress and quality of life and to analyze whether psychological distress affects the efficacy of and adverse reactions to immunotherapy combined with chemotherapy. Results: The Objective Response Rate (ORR) and Disease Control Rate (DCR) of the psychological distress group were 6.1% and 48.5%, respectively, and those of the no psychological distress group were 17.6% and 82.4%, respectively. The differences were statistically significant (χ2 = 9.026, P<0.05). The Progression-Free Survival (PFS) of advanced NSCLC patients who received immunotherapy combined with chemotherapy in the no psychological distress group was significantly better than that in the psychological distress group (HR, 0.458; 95% CI, 0.296-0.709; P<0.05). After immunotherapy, the summary score for quality of life in the psychological distress group was 1.71±.30 points, the summary score for quality of life in the no psychological distress group was 1.22±.16 points, and the difference between the groups was statistically significant (t=8.317, P<0.05). There was a significant negative correlation between psychological distress and quality of life in the 67 patients. Conclusion: Psychological distress in advanced NSCLC patients affects the efficacy of and adverse reactions to immunotherapy combined with chemotherapy, and psychological distress is negatively correlated with quality of life during immunotherapy.